The B Words - Kagerer, Tricia (Tantor Media, Inc., 2021)
Navigating the workforce as a woman can feel like making your way through a minefield. Step too far in one direction, and suddenly, you're considered bossy and overbearing and difficult to work with. Too far in the other, and you lose your power and voice. And if you try to stay in the middle, you could still be contributing to generations' worth of a stagnant mindset that has hindered women from reaching true equality. In The B Words: 13 Words Every Woman Must Navigate for Success, Tricia Kagerer uses her experience and the experiences of other women to provide guidance to help women of all ages and in all walks of life achieve their goals. Kagerer identifies the challenges-both internal and external-that hold women back both personally and professionally, explores their impact, and outlines strategies for overcoming them. Whether that means navigating difficult relationships with coworkers, building effective professional networks, or confronting one's own limiting beliefs and biases, Kagerer's advice shows how we can break through these obstacles and find our way to self-defined success. This book fights for true equality in the workforce and calls for bridges to be built not only between women but between men and women as well, fostering open communication and understanding that will lead to a brighter future.